2021
DOI: 10.37934/arfmts.88.2.113
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Palm Oil Mill Wastes Properties for Thermal Power Plants

Abstract: Renewable energy is a reliable solution for addressing global warming and fossil fuel depletion issues. Due to the abundance of biomass resources, such as palm oil wastes, which are currently underutilised, this is an opportunity for Malaysia to seize and implement this renewable energy solution for power generation. Palm oil mill wastes, such as empty fruit bunch (EFB), palm mesocarp fibre (PMF), and palm kernel shell (PKS), are worth to be investigated as a possible feedstock for combustion in thermal power … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The results showed that the temperature of direct EFB combustion reached 823 o C. Investigations into combustion in a pilot-scale boiler with a capacity of 150 kW using EFB fuel have also been carried out [26]. Research has also been discussed via wet torrefaction at temperatures up to 240°C to remove K, Ca, and Cl from EFB [27][28][29]. So far, fuel production from EFB biomass waste has generally been carried out as briquette fuel.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the temperature of direct EFB combustion reached 823 o C. Investigations into combustion in a pilot-scale boiler with a capacity of 150 kW using EFB fuel have also been carried out [26]. Research has also been discussed via wet torrefaction at temperatures up to 240°C to remove K, Ca, and Cl from EFB [27][28][29]. So far, fuel production from EFB biomass waste has generally been carried out as briquette fuel.…”
Section: Introductionmentioning
confidence: 99%
“…The transition from conventional energy transformation methods to the use of renewable energies invites us to venture into new ways of generating energy through increasingly cleaner sources [1][2][3]. As is the use of biomass material, which, being a residue of agro-industrial processes, can be used for energy generation as indicated in previous studies [4,5]. What leads to studies to generate new forms of energy transformation, is how biomass presents in its composition a high potential in its volatile material, and its fewer polluting emissions are based on a fuel that will have a high content of H 2 and not based on hydrocarbon chains that increase the carbon footprint in its emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the world is experiencing global climate change, which impacts natural disasters. This has become the most pressing environmental problem facing humanity [1,2]. The United Nations Framework Convention on Climate Change states that Indonesia is committed to contributing to global climate change solutions.…”
Section: Introductionmentioning
confidence: 99%